(untitled) (Journal of the Bangladesh Agricultural University, 2025)
Rice is the principal staple crop, securing nutritional demand for more than half of the world’s population. Due to unpredictable rainfall patterns, frequent flash floods, and higher acidity, rice production challenges are increasing day by day in Sylhet region of Bangladesh. A study was conducted in the haor area of Sylhet with 51 local and high yielding rice varieties (HYVs) in the Boro and Aman seasons. The experiment was arranged in randomized complete block design (RCBD) with three replications to observe phenology, yield characteristics, and yield of rice varieties. BRRI dhan85 (145.82 days), BRRI dhan84 (148.32 days), BRRI dhan81 (148.38 days), and local cultivars Tepi (128 days) and Rata (129 days) were short-duration Boro rice varieties. In contrast, BRRI dhan75 (117 days), BRRI dhan33 (122 days), BRRI dhan39 (126 days), and local cultivars Lalbinni (119.66 days) and Nazirshail (121 days) were short-duration Aman rice varieties. BRRI dhan29 (6.11 t ha-1), BRRI dhan28 (5.50 t ha-1), and BRRI dhan92 (5.50 t ha-1) showed maximum yield in Boro season, while BRRI dhan49 (4.59 t ha-1), BR22 (4.47 t ha-1), and BR11 (4.41 t ha-1) showed maximum yield in Aman season. BRRI Dhan85, Tepi, BRRI dhan39, and Nazirshail are short-duration and high-yielding rice varieties/cultivars among Boro HYVs, Boro local, Aman HYVs, and Aman local rice cultivars respectively. PCA revealed significant genetic variation where first three PCs accounted for 60% of total cumulative variability. PC1 and PC2 exhibited most of the variation (33% and 47% of the total cumulative variability). Cultivating these high yielding and short-duration rice could help to escape the impact of flash floods and increase the ultimate rice production in this region. J Bangladesh Agril Univ 23(2): 129-140, 2025